2018
DOI: 10.1136/bmjsrh-2017-101905
|View full text |Cite
|
Sign up to set email alerts
|

Community sexual health providers’ views on immediate postpartum provision of intrauterine contraception

Abstract: Community sexual health providers were positive towards PPIUC implementation, and perceived their role predominantly in the aftercare of women. Several clinical and practical challenges were identified, some of which differ from those previously expressed by other groups. Stakeholder involvement is key to successful implementation of PPIUC, and wider recognition of potential barriers can assist in developing strategies to overcome these.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
0
15
0
1
Order By: Relevance
“…In addition to this 17% pregnancies were mistimed, and 8% of pregnancies were unwanted [ 27 ]. Increasing access to effective postpartum intrauterine contraceptive methods can reduce the risk of unintended pregnancy and short inter-birth intervals [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this 17% pregnancies were mistimed, and 8% of pregnancies were unwanted [ 27 ]. Increasing access to effective postpartum intrauterine contraceptive methods can reduce the risk of unintended pregnancy and short inter-birth intervals [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such findings highlight the importance of engaging breastfeeding specialists in immediate postnatal contraception initiatives 42. A recent study assessing the views of 156 UK community sexual health providers found support for promotion and provision of thread checks for PPIUC but also reported challenges around staffing, knowledge and experience, and access to ultrasound 9. Referral pathways and funding for aftercare of immediate PPIUC were also highlighted as barriers.…”
Section: Resultsmentioning
confidence: 99%
“…SRH clinicians and general practitioners have an important role in training and championing postpartum contraception services. 10 In addition, for women who have had a postpartum IUD insertion, the follow-up thread check can be managed in a community setting.…”
Section: Planning For Successful Provision In Maternity Servicesmentioning
confidence: 99%